Combating the Spread of Coronavirus by Modeling Fomites with Depth Cameras - Wilson, Andrew D. (Proceedings of the ACM on Human-Computer Interaction, 2020)
Coronavirus is thought to spread through close contact from person to person. While it is believed that the primary means of spread is by inhaling respiratory droplets or aersols, it may also be spread by touching inanimate objects such as doorknobs and handrails that have the virus on it ("fomites''). The Centers for Disease Control and Prevention (CDC) therefore recommends individuals maintain "social distance'' of more than six feet between one another. It further notes that an individual may be infected by touching a fomite and then touching their own mouth, nose or possibly their eyes. We propose the use of computer vision techniques to combat the spread of coronavirus by sounding an audible alarm when an individual touches their own face, or when multiple individuals come within six feet of one another or shake hands. We further propose using depth cameras to track where people touch parts of their physical environment throughout the day, and a simple model of disease spread among potential fomites. Projection mapping techniques can be used to display likely fomites in realtime, while headworn augmented reality systems can be used by custodial staff to perform more effective cleaning of surfaces. Such techniques may find application in particularly vulnerable settings such as schools, long-term care facilities and physician offices.